Short- and long-term complications of bariatric surgery - Miguel Licea Videaux; Roberto Santana Caballero; Jesús Javier Sánchez Mata; Isabel García Morales; Dania Piñeiro Pérez; Daryl Rodríguez Denis (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Obesity affects mostly young men and women, both in developed and developing countries. Pharmacological treatments have proven to be ineffective, leaving surgery as the only therapeutic option. Bariatric procedures, despite being performed by minimally invasive surgery, are not free from presenting postoperative complications. The objective of this article is to carry out a critical analysis of the short and long-term postoperative complications of bariatric surgery. A bibliographic review of case reports and series, as well as bibliographic reviews was carried out; in English, Spanish and Portuguese, published from January 2005 to November 2022, in national and international journals indexed in recognized databases. The keywords used were: laparoscopic surgery, bariatric surgery and postoperative complications. The most widely performed and widely accepted surgical procedures are the gastric sleeve and gastric bypass. The main short-term complications are: anastomotic leakage, staple line failure, fistulas and gastrointestinal bleeding. Long-term complications are given by: anemia, vitamin and mineral deficiency, gastric sleeve stenosis, internal hernias and gain of body weight.